MP13: IMPORTANT ROLE OF PROTHROMBIN TIME (PT) AND PARTIAL THROMBOPLASTIN TIME (PTT) IN PREDICTING TPA-RELATED HEMORRHAGIC TRANSFORMATION. Issue 3 (March 2016) - Deng, W; Wickham, T; McMullin, D; Feeney, K; Buonanno, FS; Lo, EH; Ning, M
Abstract : Purpose of Study: IV tPA is not routinely followed by blood work due to its reputed short half life. While there has been much focus on tPA's extra-vascular effects on the neurovascular unit in the context of hemorrhagic transformation (HT), little is known about its intravascular efficacy, where it has its intended effect. Emerging data suggest that tPA may be most effective in microvasculature and IV therapy may be a good adjunct to intra-arterial therapy. We previously found that the effect of tPA can last more than 72 hr after stroke onset. Now, we report that even routine blood labs can potentially predict HT. Methods Used: 72 storke patients with IV tPA were recruited on IRB approval. Clinical coagulation profile (PT, PTT, fibrinogen and D-dimer) were performed at 12, 24, 72 hr post tPA. Patients on medications (e.g. anticoagulants) or with conditions (e.g. liver dysfunction, infection) that may affect these labs were excluded. Summary of Results: Compared to those without HT, HT patients had significantly higher PT and PTT (Fig A, B) as early as 12 hr post IV tPA and throughout the first 3 days of treatment. ROC analysis suggested PT/PTT at 12 and 24 hr has potential to predict tPA-induced HT (Fig C, D. PT: AUC=0.848, p=0.001; PTT: AUC=0.877; p=0.003). Conclusions: Higher PT/PTT level within 72 hr of IV tPA is early marker of tPA-induced HT. Whether these routine labs have value in symptomatic hemorrhage will require further study in a larger cohort. But this proof-of-concept study suggests that tPA efficacy can potentially be followed in real time. The development of a reliable blood test would be of clinical utility to gauge thrombolytic efficacy in real time to guide and triage adjunct treatments. Figure. No caption available.